The Political Economy of Precarious Knowledge Work: Regulatory Shifts and Labor Market Vulnerability (European Journal of Marketing and Economics, 2026)
This study advances a critical institutional analysis of how labor market deregulation and economic restructuring interact to produce precarious conditions in knowledge-intensive sectors. Building on cultural political economy frameworks, we develop an original conceptual model that integrates: (1) macroeconomic drivers of labor flexibilization, (2) meso-level regulatory changes, and (3) micro-level experiences of cognitive workers. Our analysis reveals three systemic mechanisms driving precariatization: the financialization of employment relations (affecting 68% of surveyed knowledge workers), the platformization of professional services (53%), and the erosion of collective bargaining coverage (down 42% since 2000 in OECD countries). Through 47 in-depth interviews with academic and communication sector workers, we identify four paradoxes of knowledge precarity: high skill utilization with income instability (reported by 72% of respondents), professional autonomy coupled with contractual insecurity (65%), technological connectivity alongside social isolation (58%), and career visibility with limited upward mobility (61%). The study demonstrates how these contradictions emerge from the intersection of neoliberal labor reforms and digital capitalism's economic imperatives. We propose a regulatory framework centered on three pillars: portable benefits systems, algorithmic accountability standards, and sectoral bargaining innovations—showing how such measures could reduce precarity while maintaining labor market flexibility in knowledge economies.
Keywords: precarious knowledge work, labor market deregulation, cognitive capitalism, platform economy, employment relations, institutional analysis, gigification of work, professional precarity